The Nutritional Status of Pediatric Patients with Single Ventricle Undergoing a Bidirectional Glenn Procedure - Luo, Wen-Yi (Pediatr Cardiol, 2020)
Single ventricle (SV) physiology is associated with growth retardation in children. The nutritional status of pediatric patients with SV undergoing a bidirectional Glenn (BDG) procedure vitally affects the feasibility of the next operation stages. To explore the nutritional status and to identify specific anthropometric parameters relevant to short-term surgical outcomes in children with SV after the BDG procedure, this study included 151 patients who underwent the BDG procedure. Anthropometric assessments and Infant and Child Feeding Index (ICFI) scores were used to evaluate nutritional status. There was a significant statistical correlation between ICFI and malnutrition in both the height-for-age Z-score (HAZ) and weight-for-age Z-score (WAZ) groups (P < 0.05). The clinical data, including ventilation time, nosocomial infection presence, pressure injury presence, peritoneal dialysis status, and total intensive care unit days, after BDG surgery were significantly different among the HAZ groups (P < 0.05), while nosocomial infection was different among the WAZ groups (P < 0.05). Children after BDG procedure had a high incidence of malnutrition, in addition to disease factors, the type and frequency of dietary intake were also important factors leading to worse clinical outcomes during hospitalization. Therefore, it is vital to maintain an optimal nutritional status in infants with SV who are undergoing a series of surgical procedures.